Meningkatkan Kuat Tekan Beton Dengan Menggunakan Material Recycle Concrete Aggregate (RCA): Increase Concrete Compressive Strength By Using Recycle Concrete Aggregate (RCA) Material - Zendy Bima Mahardana; Widy Rilo Pambudi; Oda Firma Emilia; Reiga Firhan Fasyaro; Andini Dwi Aprinia; Dinar Tiffani Mustafa; Meisela Induwati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Concrete is part of the building structure used in various large-scale infrastructure projects. concrete composed mixture of cement, fine aggregate, coarse aggregate, and water. Concrete able to withstand compressive forces optimally, concrete also has a smaller tensile strength than steel structures. excessive use corals causes availability materials to be depleted, is necessary to innovate continuously with use RCA. RCA is waste concrete recycled into aggregates can be reused to make concrete. The purpose is to determine the compressive strength value in concrete by replacing coarse aggregates from concrete waste measuring 19.05 mm (sieve no. 3/4). The method used experimental method by making a test object form of a cylinder with tests including testing of moisture content, sludge content, wear, and compressive strength concrete. The results obtained a normal concrete slump value 11 cm. While the concrete waste 4.4 cm. From the results were obtained according to the plan where in normal concrete was worth 17,444 Mpa and in concrete with the use of coarse aggregates from concrete waste showed a compressive strength result of 24,653 Mpa. So that shows the use waste concrete material is able to produce good concrete quality with a higher compressive strength value than normal concrete